Pengelolaan Potensi Desa (Studi Kasus Objek Wisata Di Desa Tanjung Limau) - Putri Nainggolan, Azheza (Jurnal Ilmu Pemerintahan, 2025)
Desa Tanjung Limau has many beaches. However, out of all the beaches, the government only contributes to one event held at Pantai Jingga, and that is only for parking fees. Beyond that, the village government has no contribution in the management of the beaches in Desa Tanjung Limau.  The beaches in Desa Tanjung Limau are also owned individually by the community, so the tourist attractions (beaches) in Desa Tanjung Limau do not increase the village's income.  Which should ideally make tourism one of the opportunities to increase the village's income.  The role of the village government in managing the village's potential (tourist attractions) to increase village income, after being analyzed based on interviews, is found to be very crucial in providing legal certainty, clarifying the distribution of contributions and levies, and ensuring the management of village potential is viewed from the indicators of planning, organizing, implementing, and supervising sustainably.  The Village Government is not involved at all in the management of the tourist attraction, which indirectly results in a lack of income for the village and the surrounding community because it is only managed by POKDARWIS, formed by DISPAR Kukar.